Relationship mastoid pneumatization and eustachian tube shape with tympanic cavity in chronic otitis media - Herjanto, Ferry; Naftali, Zulfikar; Santosa, Yanuar Iman; Hendaraningrum, Farah (Oto Rhino Laryngologica Indonesiana, 2022)
ABSTRACTBackground: Chronic suppurative otitis media (CSOM) is one of the causes of morbidity and mortality in developing countries. The worldwide prevalence of CSOM according to WHO is estimated at 330 million people. Pneumatic type mastoid pneumatization, narrow Eustachian tube angle, and narrow Eustachian tube diameter in the diseased ear can result in cholesteatoma formation. Objective: This study aimed to determine the relationship between mastoid pneumatization, Eustachian tube angle and diameter with tympanic cavity abnormalities in CSOM patients. Methods: This was a retrospective analysis study using cross sectional method. The data were taken from the patient’s medical records at Dr. Kariadi Hospital, Semarang, from January 2020 to June 2021. Subjects were CSOM sufferers. Mastoid multisliced computed tomography (MSCT) scan examination was carried out in the Radiology Section, using the AW Volume Share 5 application, to assess the type of mastoid pneumatization, Eustachian tube angle, Eustachian tube diameter, and tympanic cavity abnormalities in the form of cholesteatoma, granulation, and erosion of the ossicles. Statistical analysis using Chi Square test, and multivariate test. Result: There were 90 subjects with CSOM, 44 (48.9%) had tympanic cavity abnormalities and 46 (51.1%) without tympanic cavity abnormalities. Sclerotic mastoid pneumatization was more than pneumatic (p=0.001), narrow Eustachian tube angle (p=0.041), and narrow Eustachian tube diameter (p=<0.001). Logistic regression results showed that mastoid pneumatization had a dominant relationship to abnormalities in the tympanic cavity. Conclusion: There was a relationship between sclerotic mastoid pneumatization, narrow Eustachian tube angle, and narrow Eustachian tube diameter with abnormalities in the tympanic cavity. ABSTRAKLatar belakang: Otitis media supuratif kronik (OMSK) merupakan salah satu penyebab morbiditas serta mortalitas di negara berkembang. Prevalensi OMSK menurut WHO di seluruh dunia diperkirakan 330 juta orang. Pneumatisasi mastoid tipe pneumatik, sudut tuba Eustachius yang sempit, dan diameter tuba Eustachius yang lebih sempit pada telinga yang sakit dapat menyebabkan terjadinya kolesteatoma. Tujuan: Penelitian bertujuan untuk mengetahui hubungan pneumatisasi mastoid, sudut dan diameter tuba Eustachius dengan kelainan kavum timpani pada penderita OMSK. Metode: Merupakan penelitian analisis retrospektif menggunakan metode cross sectional. Data diambil dari rekam medis pasien di RSUP Dr.Kariadi Semarang, dari Januari 2020 sampai Juni 2021. Subjek adalah penderita OMSK. Pemeriksaan multisliced computed tomography (MSCT) scan mastoid dilakukan di Bagian Radiologi, dengan aplikasi AW Volume Share 5, untuk menilai jenis pneumatisasi mastoid, sudut tuba Eustachius, diameter tuba Eustachius, dan kelainan kavum timpani berupa kolesteatoma, granulasi, dan erosi pada osikula. Analisis statistik menggunakan uji Chi Square, dan uji multivariat. Hasil: Didapatkan 90 subjek penderita OMSK, adanya kelainan kavum timpani 44 (48,9%) dan yang tidak adanya kelainan kavum timpani 46 (51,1%). Pneumatisasi mastoid sklerotik lebih banyak daripada pneumatik (p=0,001), sudut tuba Eustachius sempit (p=0,041), dan diameter tuba Eustachius pendek (p=<0,001. Hasil regresi logistik menunjukan bahwa pneumatisasi mastoid memiliki hubungan yang dominan terhadap kelainan pada kavum timpani. Kesimpulan: Terdapat hubungan antara pneumatisasi mastoid sklerotik, sudut tuba Eustachius sempit, dan diameter tuba Eustachius kecil dengan kelainan pada kavum timpani.